Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/pssb.200983843
|View full text |Cite
|
Sign up to set email alerts
|

Modification of response properties of the Be(0001) surface upon adsorption of a potassium monolayer: An ab initio calculation

Abstract: Collective electronic excitations associated with a potassium monolayer (1 ML) on a Be(0001) substrate are studied using ab initio evaluations of the surface response function with the use of energies and wave functions obtained from the selfconsistent pseudopotential calculations. The plasmon dispersion relations as well as real and imaginary parts of the dynamical induced charge density oscillations are presented. Comparison of the collective modes of the 1 ML K/Be(0001) system with that of a clean Be(0001) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Shockley surface states existing at the (1 1 1) surfaces of noble metals [56,149,[366][367][368][369][370][371][372][373][374] support this collective excitation, which owes its existence to the spatial coexistence of a 2DEG with a 3D electron gas. In Ag the excitation is ascribed to the screening of the Shockley surface states electrons by bulk electrons [367,375], while recent results have indicated that in both Au [150] and Cu [376] the opposite phenomenon occurs: slow bulk electrons are screened by the faster surface state electrons.…”
Section: Predictions Of Asp In (1 1 1)-oriented Ag Filmsmentioning
confidence: 91%
“…Shockley surface states existing at the (1 1 1) surfaces of noble metals [56,149,[366][367][368][369][370][371][372][373][374] support this collective excitation, which owes its existence to the spatial coexistence of a 2DEG with a 3D electron gas. In Ag the excitation is ascribed to the screening of the Shockley surface states electrons by bulk electrons [367,375], while recent results have indicated that in both Au [150] and Cu [376] the opposite phenomenon occurs: slow bulk electrons are screened by the faster surface state electrons.…”
Section: Predictions Of Asp In (1 1 1)-oriented Ag Filmsmentioning
confidence: 91%
“…At present alkali-metal adsorption on Be(0001) has been shown to distort the dispersion due to induced quantum well states. [28][29][30] It has been demonstrated in Ref. 16 that increasing exposure of Be(0001) to O 2 leads to a shift of the surface plasmon energy and a decrease of its intensity in vibration spectra acquired along the¯ M direction of the surface Brillouin zone.…”
Section: Introductionmentioning
confidence: 97%
“…During the past few decades, plasmonic excitations in nanostructures have attracted much attention in nanosciences,1–20 because they have given rise to a large number of optical applications ranging from waveguiding to chemical and biological sensing and to medical applications, such as photothermal ablation of cancer cells and tumors. Among these nanostructures, ring structures, with their inherent high degree of symmetry, continue to fascinate scientists in a wide range of disciplines 21–30.…”
Section: Introductionmentioning
confidence: 99%